Crowded Orbits - JAMES CLAY MOLTZ (Columbia University Press, 2014)
This book offers general readers and students an understanding of the competing trends of competition and cooperation in the past and present of human space activity, while also asking questions about the future. It covers scientific topics, the economics of space, and difficult debates about military security. The book does not assume any prior knowledge of space and is aimed at reaching anyone with an interest in the subject matter. Its overall focus is on possible means of avoiding dangerous conflict in this new environment, even as human activity increases. I am grateful to Columbia University Press, especially Anne Routon, for taking an interest in this topic. The approach adopted here is similar to Joseph Cirincione’s in Bomb Scare: The History and Future of Nuclear Weapons (Columbia University Press, 2007), an engaging and informative short volume on a key policy issue facing nations in a crucial arena of international relations, including the risks of future conflict. I have tried to give readers a full picture of the historical, technological, and political factors in space necessary to allow them to discuss and analyze the issues intelligently. I wrote this volume over the course of the three years from 2011 to 2013. But the book also draws on my more than twenty-five years of professional experience studying space politics and writing about their international dimension. While there is considerable academic literature on space competition and cooperation, almost all of it is written in scholarly and specialist jargon. This volume is an effort to bring the key concepts and problems to the interested public and students, who have to date been underserved in terms of accessible studies on international space policy.